Transcriptome Analysis of Microglia Reveals That the TLR2/IRF7 Signaling Axis Mediates Neuroinflammation After Subarachnoid Hemorrhage - Xu, Shenbin; Mei, Shuhao; Lu, Jianan; Wu, Haijian; Dong, Xiao; Shi, Ligen; Zhou, Jingyi; Zhang, Jianmin (Frontiers in Aging Neuroscience, 2021)
Microglia-mediated neuroinflammatory response in the early brain injury after subarachnoid hemorrhage (SAH) has been reported to have an impact on progress and the mechanism is not completely understood. Here, we performed genome-wide transcriptome analysis of microglia purified from damaged hemisphere of adult mice at 3 days after SAH or sham operation. Robust transcriptional changes were observed between SAH-induced and healthy microglia, indicating rapid activation of microglia after suffering SAH. We identified 1576 differentially expressed genes (DEGs; 928 up-regulated and 648 down-regulated) in SAH-induced microglia compared with sham microglia, representing a strong alteration of the genome (6.85% of total ~23,000 genes). Functional enrichment of these DEGs indicated that cell division, inflammatory response, cytokine production and leukocyte chemotaxis were strongly activated in SAH-induced microglia. Moreover, we identified and proved the TLR2/IRF7 signaling axis was involved in regulation of this microglia-mediated inflammation in SAH mice, by performing flow cytometry, immunofluorescence. Together, these results provided a perspective of microglia-mediated neuroinflammatory response in the early stage of SAH and might give a new therapeutic target for SAH.